Comparative Effectiveness Of Robotic-Assisted And Conventional Manual Total Knee Arthroplasty: A Systematic Review Of Functional Outcomes And Complication Rates Within Six Months In Tertiary Care Settings - Karunanithi, Krupanidhi; Subashini, R.; R, Priyadharsini; Prathap, A.; Dhivyaprasath, P. (Journal of Neonatal Surgery, 2025)
Background: Robotic-assisted total knee arthroplasty (RA-TKA) has emerged as a significant advancement in knee replacement surgery, aiming to improve how implants are positioned, align limbs better, and boost overall patient satisfaction. However, the short-term results of RA-TKA in comparison to traditional manual TKA (C-TKA) are still not completely clear. Objective: This systematic review aims to evaluate and compare the functional outcomes and complication rates within six months after surgery between RA-TKA and C-TKA in tertiary care environments. Methods: We carried out an extensive literature search across various databases, including Web of Science, EMBASE, Scopus, and PubMed, focusing on studies published between 2015 and 2025. Our selection process included randomized controlled trials, as well as both prospective and retrospective cohort studies, along with registry-based analyses that specifically looked at adult patients undergoing primary total knee arthroplasty (TKA) due to osteoarthritis or similar degenerative conditions. We evaluated outcomes such as range of motion, pain levels, validated patient-reported outcome measures (PROMs), and the rates of postoperative complications. The data were synthesized both narratively and, when appropriate, through a random-effects meta-analysis. Results: Out of 27 studies identified, 5 met our inclusion criteria. RA-TKA consistently showed lower postoperative pain, faster functional recovery, and less opioid consumption compared to C-TKA. Patient satisfaction was significantly higher with RA-TKA, although PROMs did not indicate major differences in long-term functional outcomes. The short-term complication rates, including infections and thromboembolic events, were low and similar across both groups. Conclusions: RA-TKA presents short-term benefits over C-TKA, especially in terms of early pain relief and functional recovery. However, to draw definitive conclusions about long-term functional advantages and implant longevity, we need larger-scale, high-quality studies. Individual patient factors also play a crucial role in these outcomes